Kontribusi Kecerdasan Emosional terhadap Interaksi Sosial Mahasiwa - Yogi Damai Syaputra; Monalisa Monalisa (Biblio Couns : Jurnal Kajian Konseling dan Pendidikan, 2018)
The background of this research was the importance of a college students’ guidance and counseling program in STKIP PGRI West Sumatera to have a good social interaction. Emotional intelligence became factors that can predict affect social interaction. The purpose of this research was obviously to describe: (1) emotional intelligence, (2) the contribution of emotional intelligence towards social interactions, This research was using quantitative method with correlation type. The population was college students’ guidance and counseling program in STKIP PGRI West Sumatera in academic year  2012, 2013, 2014, and 2015. A number of college students were 818 students. The sample was 272 students selected by proportional stratified random sampling technique. The instrument was a Likert scale models. The research findings shown that: (1) an average of the emotional intelligence of college students at the high category, (2) there was a significant contribution of emotional intelligence toward social interaction.Implications of these results can be used as an analysis of the college students’ needs in the preparation of guidance and counseling program services at universities, especially in STKIP PGRI West Sumatera.